1980
DOI: 10.1055/s-2008-1033856
|View full text |Cite
|
Sign up to set email alerts
|

Teil 3: Longitudinale Körperentwicklung gesunder Kinder*: Brust-, Oberarm-, Oberschenkel- und Wadenumfang von Kindern im Alter von 2,0 bis 15 Jahren

Abstract: From 1968--1978 a longitudinal study was performed concerning development of thorax, upper arm, thigh and calf circumferences in 709 boys and 711 girls 2--15 years old. In boys the mean increase in thoracic circumference amounted to 32.9 cm, in upper are circumference to 8.3 cm, in thigh circumference to 20.6 cm and in calf circumference to 13.0 cm. The corresponding circumferences in girls amounted to 30 cm, 7.9 cm, 22.4 cm and 12.7 cm. In boys the circumferences developed almost linearly until year 15. Girls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
4

Year Published

1987
1987
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 0 publications
0
12
0
4
Order By: Relevance
“…KOPS data were obtained between 1996 and 1999. These data were compared with reference for 5 to 7-y-old children in northwest Germany from 1978 published by Reinken et al 25 state. 20 In 5 to 7-y-old children there is a linear social gradient in unhealthy behaviours.…”
Section: Baseline Measurementsmentioning
confidence: 99%
“…KOPS data were obtained between 1996 and 1999. These data were compared with reference for 5 to 7-y-old children in northwest Germany from 1978 published by Reinken et al 25 state. 20 In 5 to 7-y-old children there is a linear social gradient in unhealthy behaviours.…”
Section: Baseline Measurementsmentioning
confidence: 99%
“…The height deficit increased stepwise during the first 2 years. Growth in girls with WBS was around the 3rd percentile [1][2][3]19] until age 9 years. Growth velocity data (Table 3) showed that there is a mid-growth spurt in WBS girls (increase in height velocity from 5.9 to 6.9 cm/year from age 6 to 7 years).…”
Section: Girlsmentioning
confidence: 99%
“…3b. From the age of 6 months to age 11 years mean growth followed approximately the 3rd percentile of normal [1][2][3]19]. There was no mid-growth spurt in boys (Table 3).…”
Section: Girlsmentioning
confidence: 99%
“…However, in 1995, Ranke et al L131 used the term ISS and proceeded to divide patients into those with FSS and those with CDGP according to whether height standard deviation score (SDS) was within the range for parental target height (defined as equal to or greater than a target height SDS of -1.28 SD) or below parental target height, respectively. The selection criteria are summarized in table 1, and the studies are identified as A-F. Tanner height standards |14] were usually used to select pa tients, with the exception of studies C and F, in which Ger man standards [15] were used, and study E, in which North American standards [16] were used. Auxological data for studies A -F are summarized (using mean values only for clarity) in table 2.…”
Section: Introductionmentioning
confidence: 99%